(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
While creating a new notion of everyday life, the COVID-19 pandemic also affects the resolution of cross-border family disputes, including the international child abduction cases. The return of an abducted child to the country of his or her habitual residence is challenged by travel restrictions, international border closures, quarantine measures, but also by closed courts or cancelled hearings. Those new circumstances that befell the whole world underline two issues considering child abduction proceedings. The first one considers access to justice in terms of a mere possibility of the applicant to initiate the return proceeding and, where the procedure is initiated, in terms of the manner of conducting the procedure. The legislation requires a quick initiation and a summary resolution of child abduction proceedings, which is crucial to ensuring the best interests and well-being of a child. This includes the obligation of the court to hear both the child and the applicant. Secondly, it is to be expected that COVID-19 will be used as a reason for child abduction and increasingly as justification for issuing non-return orders seen as a “grave risk” to the child under Article 13(1)(b) of the Child Abduction Convention. By analysing court practice from the beginning of the pandemic in March 2020 to March 2021, the research will investigate how the pandemic has affected child abduction proceedings in Croatia. Available national practice of other contracting states will also be examined. The aim of the research is to evaluate whether there were obstacles in accessing the national competent authorities and courts during the COVID-19 pandemic, and in which manner the courts conducted the proceedings and interpreted the existence of the pandemic in the context of the grave risk of harm exception. The analyses of Croatian and other national practices will be used to gain an overall insight into the effectiveness of the emerging guidance and suggest their possible broadening in COVID-19 circumstances or any other future crises.